TINJAUAN HUKUM FIKIH TERHADAP TRADISI SEBAMBANGAN MASYARAKAT LAMPUNG - Ramdani, Rahmatullah; Abdillah, Kazhimi; Abdullah, Hilmi Marwa; Daulima, Adi Akid; Ramadhan, Abdul Rahman (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
Lampung is one of the regions that still has a strong customary area. one of the customs in the marriage tradition of Lampung people is Sebambangan. Sebambangan or larian is where the male party takes the female party away on a consensual basis, there is an agreement between the male and female parties beforehand, and the female party will leave a letter and money as a pengepik which is usually placed under the mattress where the girl sleeps. This is an original tradition of Lampung people, a culture that has been rooted since the time of the ancestors. This can happen if the family of one of the parties does not approve of marriage plans in a normal or common way and it can also be because the Sebambangan tradition is the right choice so that marriage costs tend to be cheaper. This study aims to determine how the process of implementing sebambangan in Lampung customary society according to Islamic fiqh law. The method used in this research is a qualitative approach. The result of this research is a review of Islamic fiqh law on the sebambangan customary tradition carried out by the people of Lampung.